Implementation of Legal Provisions in Indonesia Regarding Tax Imposition - Darma, Abednego Parlindungan (Universitas Pelita Harapan, 2024)
Tax is a mandatory contribution to the state owed by an individual or entity that is coercive based on law, without receiving direct compensation and is used for state needs for the greatest prosperity of the people. The purpose of this research is to find the implementation of Indonesian legal provisions for franchise businesses in Indonesia and to find out the tax implementation of laws in Indonesia for franchise businesses. Type of research used in this research is normative research using secondary data by conducting document studies in the form of official documents, books, and research results in the form of reports. The approach taken is a statutory approach and a conceptual approach with analyses. From the research results, it is known that the implementation of Indonesian legal provisions for franchise businesses in Indonesia includes the following regulations: contract law, intellectual property rights, taxation, employment, company registration and business permits. The implementation of tax laws in Indonesia for franchise businesses is not running optimally due to obstacles in the form of a lack of government socialization regarding franchise business taxes, a lack of restaurant taxpayers' understanding of franchise tax policies, and a lack of awareness of taxpayers in paying their taxes. There is a willingness to pay where the willingness or desire of taxpayers to pay taxes is low and there is still a lot of taxpayer dishonesty in paying taxes.